Human Rights and the New Corporate Accountability: Learning from Recent Developments in Corporate Criminal Liability - Voiculescu, Aurora (Journal of business ethics, 2009)
The 3rd Report of the Special Representative of the Secretary-General of the United Nations appears to have generated significant consensus around its approach to business and human rights. This state of harmony relies mainly upon a narrow mandate limiting the endeavour largely to a mapping exercise. It also relies upon a process of ‘operationalisation’ that is yet to be undertaken despite the recent release of a 4th Report. After a brief presentation of the main parameters of the framework proposed by the 3rd Report and of its precarious advantage over other similar initiatives, this article takes a close look at the main link that needs to be operationalised: i.e. the link between corporate responsibility for human rights and the concept of legal and criminal responsibility. The article then addresses the constitutive elements of the concept of responsibility to shed light upon the responsibility of business organisations in a human rights law context. It looks at the innovative ways in which the concept of corporate criminal responsibility has been dealt with in various domestic jurisdictions and at the new paradigms of corporate agency resulting in the process. Building on this inquiry, the analysis focusses on the way in which the legal discourse acquires new dimensions of corporate responsibility by moving away from an individualistic perspective. On the basis of this, the article suggests conceptual tools that can become instrumental in the process of the operationalisation of the 3rd Report, albeit at the likely cost of rendering the consensus around it more fragile.